EMD Electricty monitoring device for user awareness - Muhamad Herman, Jamaluddin; Mohamad Azmi, Said; Marizan , Sulaiman (2008)
Electricity bill charges usually dependents on the amount of electricity usage. The increment in the electricity usage will cause the users to pay more. This situation always happens when users are not aware about their growing usage. Hence, a system is needed where it can monitor and measure the electricity usage and update users on the increasing electricity utilization. This paper will discuss about EMD research methodology and process development of a device to monitoring real-time electricity utilization. This system will indirectly help the users to monitor the amount of electricity usage which will help them to control and overcome wastage of electric power.